Exploring the relationship between pet companionship, family support, peer support, and social media support on psychological well-being among young adults in Selangor, Malaysia - Xin, Seah Kha; Marof, Aini Azeqa (Human Resource Management Academic Research Society (HRMARS), 2023)
This study investigates the complex dynamics underlying psychological well-being (PWB) among 317 young adults residing in Selangor, Malaysia. The research investigates the various determinants of PWB, with a focus on pet companionship, family support, peer support, and social media support. Using well-established measurement instruments, the study aims to elucidate the complex relationships between these variables and their collective effect on the psychological well-being of the participants. This investigation reveals significant positive correlations between PWB and each of the aforementioned support sources. First, pet companionship is associated with improved PWB, highlighting the therapeutic and emotionally enriching role that pets can play in the lives of individuals. Family support has an exceptionally strong positive correlation with PWB, highlighting the central role that familial relationships play in influencing the mental health of young adults. Peer support emerges as a powerful predictor of PWB, highlighting the central role of supportive peer networks in fostering psychological health. In addition, the study clarifies the central role of social media support in promoting PWB among respondents. Participants who perceive increased support through online interactions report higher levels of PWB, highlighting the evolving role of social media platforms as emotional and informational supports. In conclusion, these findings demonstrate the complex interaction between pet companionship, familial support, peer support, and social media support in influencing the psychological health of young adults. This research, conducted in Selangor, Malaysia, contributes significantly to the increasing body of empirical knowledge regarding the multifaceted determinants of PWB. These findings have important ramifications for the design and implementation of targeted mental health interventions and programmes tailored to improve the well-being of young adults in modern society.